The Wizard of Oud - A Case Study of Sydney-Based Oud Player Joseph Tawadros (Journal of Music Research Online, 2022)
This article is a case study of Sydney based oud player Joseph Tawadros. The discussion centres on the strategic market positioning of this musician and the use of identity as a tool for navigating patronage within the local and international music economies. This study observes the ways in which Tawadros embraces multiple identity positions, reinscribing himself and his instrument within the dominant narratives of art music in Australia, and considers how this may have helped him gain access to different forms of patronage. By reference to media interviews and interviews conducted with the author, this case study presents him as a musician who skilfully adopts and invokes various musical identities and identities tied to nationalism. These have helped Tawadros navigate diverse musical categories and mainstream media. This paper uses the Tawadros case study to explore the strategies used by musicians associated with World Music, Multicultural arts and Culturally and Linguistically Diverse arts in Australia.